The prevalence of cardiovascular risk factors in the young and middle-aged rural population in Sarawak, Malaysia - Chang, Ching Thon; Lee, Ping Yein; Cheah, Whye Lian (Penerbit Universiti Sains Malaysia, 2012)
Background: Coronary heart disease (CHD) was the second leading cause of death in Malaysia in 2006. CHD has known risk factors including hypertension, diabetes mellitus, and obesity. Methods: This cross-sectional study examined the prevalence of cardiovascular risk factors among 260 participants aged 20 to 65 years in a rural community in Sarawak. Results: The prevalences of overweight and obesity in this study were 39.6% and 11.9%, respectively. Approximately 13% of participants had hypertension, and 1.5% had a random blood sugar greater than 11.1 mmol/L. Chi-square tests showed significant associations between obesity and gender (P = 0.007), low high-density lipoprotein cholesterol and race (P = 0.05), high total cholesterol and age (P = 0.007), age and hypertension (P = 0.011), smoking and gender (P < 0.001), and smoking and income (P = 0.050). Age-adjusted logistic regression showed that women were 0.246 times more likely to be obese, that older participants (> 45 years) were 0.395 times more likely to have high cholesterol and that those with a higher monthly household income (> RM830) were 2.471 times more likely to smoke. Conclusion: These findings indicate that we should be concerned about the high rates of overweight in this rural community to prevent obesity.